Long-term palliation of lymph node oligometastatic ovarian carcinoma after repeated stereotactic body radiotherapy: case report. Issue 6 (December 2020) - Trippa, Fabio; Draghini, Lorena; di Marzo, Alessandro; Anselmo, Paola; Arcidiacono, Fabio; Terenzi, Sara; Sivolella, Silvio; Bassetti, Alessandra; Sdrobolini, Andrea; Maranzano, Ernesto
Introduction: Oligometastatic disease has emerged as an intermediate state between localized and systemic cancer. Improvements in diagnostic modalities such as functional imaging allow a greater frequency of oligometastases diagnosis. Patients with selected oligometastatic epithelial ovarian carcinoma (EOC) may be treated with metastasis-directed stereotactic body radiotherapy (SBRT) rather than chemotherapy. Case description: We describe a 58-year-old woman who underwent surgery and chemotherapy for an EOC. The patient underwent 3 chemotherapy lines for recurrence of disease, but had allergic reactions and serious hematologic toxicity. During follow-up, lymph node oligometastases were diagnosed and treated with repeated SBRT because the patient refused further chemotherapy. No side effects were observed after each course of SBRT and the patient obtained complete response of all irradiated sites. Conclusions: SBRT is a promising treatment approach for recurrent oligometastatic EOC with a high control rate and irrelevant iatrogenic toxicity. The possibility to repeat SBRT courses when new oligometastases are encountered in other sites resulted in an adequate long-term palliation approach.